Relationship Between Instructor Andragogy Competency and Learning Outcomes of English Training Participants at LKP Hazika Education Centre Padang - Fany Saripadillah; Wirdatul Aini (Universitas Negeri Padang, 2023)
This research is motivated by the low learning outcomes of English training participants at LKP Hazika Education Center Padang. The aims of this research are to find out (1) to describe Andragogy Competence, (2) To describe the learning outcomes of English training participants at LKP Hazika Education Center Padang, (3) To see the relationship between Instructor Andragogy Competence and Learning Outcomes of English Training Participants. at LKP Hazika Education Center Padang. This type of research is a quantitative descriptive correlational research. The population of this study was the participants of the English language training at LKP Hazika Education Center Padang, totaling 30 people and a sample of 65%, namely 20 people using the Stratifed Random Sampling technique. The data collection technique used is a questionnaire and the tool used is a list of questions. The data analysis technique used the percentage formula and the Spearmen Rho formula. The results of this study indicate that: 1) Instructor Andragogy Competence at LKP Hazika Education Center Padang is categorized as low. 2) Learning outcomes of English training participants at LKP Hazika Education are still low. 3) there is a significant relationship between the relationship between the Instructor's Andragogy Competence and the Learning Outcomes of English Training Participants at LKP Hazika Education Center Padang. The suggestion of this research is to the managers of the course and training institutions to further improve the quality of learning in English language training. To instructors in order to improve competence as educators, especially andragogy competence in English language training.Keywords: Andragogy Competence, Learning Outcomes